Pengembangan Media Pembelajaran Audio Visual PPKn Muatan Persatuan dalam Keberagaman - Putu Indah Lestari; I Nengah Suastika (ILIN Institute Makassar, 2021)
This study aimed to develop an audio-visual learning media for Civics with the content of Unity in Diversity in grade 2 of elementary school. This research was a type of development research using the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. The research instrument consisted of a material expert validator questionnaire, learning media expert, and small group limited test. The test subjects used in this study were expert validation (material experts, learning media experts) and ten 2nd graders of Cipta Dharma Denpasar Elementary School. The data analysis technique used was quantitative and qualitative five-scale descriptive statistics. The study result indicated that: 1) the results of the material expertise got the media suitability with the Standard Competency/Basic Competency of 94.29% in the very appropriate, very feasible, very valid category. In terms of content indicators and material clarity, it was 85.71% with appropriate, feasible, and valid categories. Meanwhile, based on the indicators of conformity with the level of cognitive and moral development, it was 88.57% in the appropriate, feasible, and valid category. 2) Validation test by learning media experts on layout indicators, cover attractiveness, background selection was 91.43% in the very appropriate, very feasible, and very valid categories. While the ease of use indicator was 88, 57% appropriate, feasible, and valid category. 3) The small group trial obtained an average percentage of 92% with very appropriate and very appropriate categories. It could be concluded that the development of learning media for unity in diversity was feasible and valid used as teaching material for Civics in elementary schools.